2014
DOI: 10.3109/02770903.2014.920875
|View full text |Cite
|
Sign up to set email alerts
|

In-school asthma management and physical activity: children’s perspectives

Abstract: OBJECTIVE Regular physical activity (PA) is an important component of pediatric asthma management. No studies have examined how in-school asthma management influences PA from children’s perspectives. The aim of this study was to explore children’s perceptions of the impact of in-school asthma management on PA. METHODS Qualitative interviews with 23 inner-city minority children with asthma (ages 8–10 yrs; 12 girls, 11 boys) were conducted in 10 Bronx, New York elementary schools. Sampling continued until satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 27 publications
1
27
0
4
Order By: Relevance
“…[13, 25] Interestingly, while the majority of caregivers reported living within walking distance of a playground or park, more than 1/3 reported that there is no safe place to exercise near their home and few children frequented outdoor play areas. Thus, in addition to activity limitation there are also environmental barriers to attaining physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…[13, 25] Interestingly, while the majority of caregivers reported living within walking distance of a playground or park, more than 1/3 reported that there is no safe place to exercise near their home and few children frequented outdoor play areas. Thus, in addition to activity limitation there are also environmental barriers to attaining physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, qualitative research with children aged 8–10 years in New York showed that school management of inhalers and poor asthma control were key factors that affected physical activity participation 22. Similarly, Brazilian data have shown that 96% of mothers of children aged 9–19 years and young people with asthma reported that they felt that physical activity was important for their child but 37% of the sample restricted their child's physical activity opportunities 23.…”
Section: Discussionmentioning
confidence: 99%
“…Group workshops provide adolescents the opportunity to share the burden of their illness and to learn how others cope with asthma 23. Incorporating asthma education into the health curriculum at school can raise awareness about asthma and children with asthma may feel less hesitant or embarrassed to take medication at school 24. Families of smoke-exposed children should receive an environmental tobacco smoke reduction program aimed at motivating smoking cessation among family members and decreasing their child’s exposure to environmental tobacco smoke 14…”
Section: Discussionmentioning
confidence: 99%